A Sociolinguistics Analysis on Slang and Technological Neologisms in Darren Watkins’ (IShowSpeed) Gaming Livestreams on YouTube - Adika Indotua Nainggolan; Yolanda Jesica Sitanggang; Leony Elisabet Situmorang; Tessaria Simorangkir; Monika Natalina Silaban; Tiarma Intan Marpaung (JURNAL ILMIAH NUSANTARA, 2026)
This study investigates how slang and technological neologisms are formed and used in Darren Watkins’ (IShowSpeed) gaming livestreams on YouTube, focusing on one full gameplay session of The Last of Us Part II. Drawing on a qualitative descriptive approach, the study collects lexical items from the livestream transcript and classifies them using Lazore’s (2017) fivefold framework of blends, abbreviations and acronyms, clippings, repurposing of standard English, and coinage of new terms. The analysis distinguishes between general English slang influenced by broader internet culture and specialized gaming slang tied to gameplay mechanics and technological environments, as summarized in two tables of lexical items. Findings show that abbreviations and clippings (e.g., AFK, GG, PC, ult, stats) dominate the data, indicating a strong pressure toward linguistic economy and rapid real-time communication. Repurposed English terms (e.g., dead, stream died, carry, feed, grind) reveal systematic semantic shifts that rely on shared cultural knowledge within the streamer–audience speech community. Coinages and blends (e.g., nerf, buff, gank, lagspike) highlight the creative and community-specific nature of gaming discourse. Overall, the study argues that IShowSpeed’s livestream functions as a socio-technical space where lexical innovation is driven simultaneously by efficiency, identity construction, and technological mediation, illustrating how digital gaming culture actively reshapes contemporary English vocabulary